Efektifitas Penerapan Metode Microlearning untuk Meningkatkan Hasil Belajar Mahasiswa : Effectiveness of Microlearning Method Implementation to Improve Student Learning Outcomes - Pebriantika, Leni; Rahmi, Juhaidatur; Adesti, Anita; Eriyanti, Eriyanti (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to determine the effectiveness of applying the microlearing method on student learning outcomes. This type of research is quantitative research with experimental methods and pre-experimental design, with the form of one-group treatment, pre-test-post-test. When conducting experiments, before entering the learning material, questions are given (Pre-test), and after the material activities are given questions again (Posttest). The population in this study were 5th (fifth) semester students of the Baturaja University Educational Technology Study Program in the 2024/2025 academic year, totaling 25 people. The sample technique used was Total Sampling. Data collection techniques using learning outcomes test as many as 20 items). Data analysis techniques using t-test. The acquisition of test results before the application of the microlearning method (pre-test) the average value is 61.4. While the data of the test results after (post-test) the average value is 88.00. This proves an increase in student learning outcomes after the application of the microlearning method. After testing the hypothesis, it is known that the value of Sig. (2-railed) is 0.000 <0.005. The df value is 24, so the t-table value = 2.064. The t-count value = 13.779 then the t-table < t-count is 2.064 < 13.779. It can be concluded that there is a significant difference between the pre-test and post-test scores of student learning outcomes. This means that the results show significant and the microlearning method is effective to use in learning.